Sleep-disordered Breathing in Uncontrolled Blood Pressure: Our Experience - Sijapati, Milesh Jung; Pandey, Minalma; Khadka, Nirupama; Karki, Poojyashree (Nepalese Medical Journal, 2018)
Introduction: Sleep-disordered breathing is one of the greatest health problems. It comprises of obstructive sleep apnea, central sleep apnea, periodic breathing, and upper airway resistance syndrome. There are several studies reporting association of uncontrolled blood pressurewith individuals having sleep disordered breathing. Data regarding this were sparse in developing countries. Therefore this study was performed to find out the sleep-disordered breathing among uncontrolled hypertensive patients. Materials and Methods: Study was performed from January, 2014 to January, 2017 in sleep center in Kathmandu, Nepal. Patient with uncontrolled BP were included. Uncontrolled BP was defined as blood pressure>130/80mmHg not on intensive antihypertensive regimen and resistant elevated BP was defined as blood pressure >130/80 mmHg despite intensive antihypertensive regimen. These patients were subjected for polysomnography. Results: Three hundred patients were selected out of which 250 patients with uncontrolled blood pressure were included. They were subjected for overnight polysomnography. Among them, 70patients (28%)were found to have mild obstructive sleep apnea, 20 patients had moderate obstructive sleep apnea (8%)&15 had severe obstructive sleep apnea (6%). Conclusions: This study concludes that those individuals having uncontrolled blood pressure has obstructive sleep apnea and these individuals have to undergo polysomnography. Nepalese Medical Journal, vol.1, No. 1, 2018, page: 36-38